Cost-effectiveness analysis of double low-dose budesonide and low-dose budesonide plus montelukast among pediatric patients with persistent asthma receiving Step 3 treatment in China. (1st December 2020) - Wang, Xiaoling; Fang, Honghao; Shen, Kunling; Liu, Tianyi; Xie, Jipan; Liu, Yuantao; Wu, Peibei; Chen, Yilin; Zhong, Jia; Wu, Eric; Zhou, Wei; Wu, Bin
Abstract: Aims: For children aged 1–5 years with persistent asthma, double low-dose inhaled corticosteroids (ICS) are recommended as the preferred Step 3 treatment and low-dose ICS plus leukotriene receptor antagonists (LTRA) as an alternative. Budesonide inhalation suspension (0.5 mg daily) and montelukast (4.0 mg daily) are commonly used low-dose ICS and LTRA, respectively, among children in China. This study compared the cost-effectiveness of double low-dose budesonide vs. low-dose budesonide plus montelukast from a Chinese healthcare payer's perspective. Methods: A Markov model was constructed with four health states (i.e. no exacerbation, mild exacerbation, moderate-to-severe exacerbation, and death). Transition probabilities were estimated based on exacerbation rates, case-fatality of hospitalized patients due to exacerbation, and natural mortality. Treatment adherence was considered and assumed to impact both drug costs and exacerbation rates. Costs (in 2019 Chinese Yuan [¥]) included drug costs and exacerbation management costs. Cost inputs and utilities for each health state were obtained from a public database and the literature. In-depth interviews were conducted with a health economics expert to validate the model, and a clinical expert to verify inputs and assumptions related to clinical practice. Costs and quality-adjusted life-years (QALYs) were estimated over a year. Deterministic and probabilistic sensitivity analyses were performed. Results: Compared with low-dose budesonide plus montelukast, double low-dose budesonide was associated with lower costs (¥1, 534 vs. ¥2, 327), fewer exacerbation events (0.43 vs. 1.67) and slightly better QALYs (0.98 vs. 0.97). Sensitivity analyses supported the robustness of the results and the generalizability of findings across geographic regions in China. Conclusion: The cost-effectiveness analysis suggests that double low-dose budesonide is a dominant Step 3 treatment strategy compared with low-dose budesonide plus montelukast for patients aged 1–5 years with persistent asthma in China.